Na+ and K+ transport and maturation stage ameloblast modulation - Ngu, Jake; Bronckers, Antonius L. J. J.; Katsura, Kaitlin; Zhang, Yan; Den Besten, Pamela K. (Frontiers in Physiology, 2023)
Enamel mineralization requires calcium transport into the extracellular matrix for the synthesis of hydroxyapatite (HA) crystals. Formation of HA releases protons into the matrix, which are then neutralized when ameloblasts modulate from cells with apical invaginations, the so-called ruffle-ended ameloblasts (RE), to smooth-ended ameloblasts (SE). Ameloblast modulation is associated with the translocation of the calcium exchanger Nckx4 to the apical border of RE, to remove Na+ from the enamel matrix in exchange for Ca2+ and K+. As enamel matures, Na+ and K+ in the matrix progressively decrease. However, the transporter to remove K+ from mineralizing enamel has not been identified. Expression of K+ exchangers and channels in secretory and maturation stage of enamel organs were compared following an RNA-seq analysis. Kcnj15, which encodes the Kir4.2 inwardly rectifying K+ channel, was found to be the most upregulated internalizing K+ transporter in maturation stage of enamel organs. Kir4.2 immunolocalized to the apical border of wild type (wt) mouse RE and cytosol of SE, a spatial distribution pattern shared by NCKX4. In Nckx4-/- ameloblasts, Kir4.2 also localized to the apical surface of RE and cytosol of SE. However, in fluorosed and Wdr72-/- ameloblasts, in which vesicle trafficking is disrupted, Kir4.2 remained in the cytosol. In vitro, Wdr72 was upregulated in LS8 cells cultured in medium with a pH 6.2, which is the pH of the enamel matrix underlying RE, as compared to pH 7.2 under SE. Taken together these results suggest that Kir4.2 participates in K+ uptake by maturation ameloblasts, and that K+ and Na+ uptake by Kir4.2 and Nckx4, respectively, may be regulated by pH through WDR72-mediated endocytosis and membrane trafficking.